Like Joseph in beauty : Yemeni vernacular poetry and Arab-Jewish symbiosis - Wagner, Mark S. (Brill Studies in Middle Eastern Literatures, 2009)
Like Joseph in Beauty traces the evolution of an Arabic poetic form called 'Humayni poetry'. From Muslim mystical circles, the courts of aristocrats in Highland Yemen, and kabbalist circles of Yemenite Jews, Humayni poetry distinguishes itself with lyricism, musicality, and eroticism. It also plays a variety of code-switching linguistic games. The book addresses the connections between the Humayni poetry of Yemen and the sacred poetry of Jews from Yemen, a hitherto-neglected chapter in the history of Arabic and Jewish literatures. The book culminates with a discussion of ways in which poets and critics in modern-day Yemen and in Israel transformed this poetry.